Simultaneous Wireless Information and Power Transfer Over KG Fading Channels - Deka, Nandita; Subadar, Rupaban (International Journal of Integrated Engineering, 2022)
In this paper, we proposed a novel expression for the probability density function (PDF) and the cumulative density function (CDF) of the output SNR for the M-branch Selection Combining (M-SC) receiver over Generalized-K (KG) fading channels. Unlike conventional energy sources, the proposed scheme uses a Power splitter (PS) scheme at the receiver side. The received signal is split into information decoding and energy harvesting receiver with adjustable power levels. The expressions of our system consider arbitrary channel parameters and diversity branches. We analyze the proposed model and derive the closed-form expression for average SNR and average bit error rate (ABER) to evaluate the system performance. The obtained results are corroborated with the help of Monte-Carlo simulations. The effects of system parameters, such as power splitter ratio, modulation order, and shaping parameters of KG fading channels, are studied. This type of system will benefit reliable data transmission in an energy-limited scenario.